2019
DOI: 10.3389/fict.2019.00001
|View full text |Cite
|
Sign up to set email alerts
|

Touchy : A Visual Approach for Simulating Haptic Effects on Touchscreens

Abstract: Haptic enhancement of touchscreens usually involves vibrating motors producing limited sensations or custom mechanical actuators that are difficult to disseminate. In this paper, we propose an alternative approach called "Touchy," where a symbolic cursor is introduced under the user's finger, to evoke various haptic properties through changes in its shape and motion. This novel metaphor enables to address four different perceptual dimensions, namely: hardness, friction, fine roughness, and macro roughness. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…We applied vibration to produce the tactile sensation of unevenness. Touchy [11] suggested that vibrating a white cursor on a display made users feel the sensation of unevenness. In our Shaking-finger effect, only the fingertip of the pointing finger shakes.…”
Section: ) Shaking-fingermentioning
confidence: 99%
See 1 more Smart Citation
“…We applied vibration to produce the tactile sensation of unevenness. Touchy [11] suggested that vibrating a white cursor on a display made users feel the sensation of unevenness. In our Shaking-finger effect, only the fingertip of the pointing finger shakes.…”
Section: ) Shaking-fingermentioning
confidence: 99%
“…Lecuyér et al [10] showed that in a mouse/display system, users felt frictional force by changing the control/display (C/D) ratio of a virtual object manipulated by the users when the virtual object crossed an area. Touchy [11] provided users with tactile textures for images displayed on a touch panel by changing the shape and movement of a white ring drawn on the panel. These studies suggest that users can feel tactile sensations of objects from virtual hand interfaces with pseudo-haptic feedback, which has not yet been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“…So far, pseudo-haptic feedback has been studied in situations, where a user manipulates a virtual object (e.g., a cursor) by operating a computer mouse ( Lécuyer et al, 2004 ; Dominjon et al, 2005 ; Kumar et al, 2017 ), tablet PCs ( Ujitoko et al, 2015 ; Costes et al, 2019 ), pen devices ( Ujitoko et al, 2019a , b ), virtual hands ( Sato et al, 2020 ), real objects ( Brewster et al, 2019 ), and mixed reality technologies ( Ban et al, 2012 ; Issartel et al, 2015 ; Kawabe, 2020 ). The use of these devices involves hand movements that are more or less consistent in direction with the movement of the virtual object.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we attempted to specify stimulus conditions that would provide a sense of resistance to a user who manipulated a cursor only using keystrokes. In previous studies, pseudo-haptic feedback has been discussed in terms of physical properties such as friction ( Lécuyer et al, 2000 ; Ujitoko et al, 2019a ), mass ( Dominjon et al, 2005 ; Issartel et al, 2015 ; Yu and Bowman, 2020 ), and viscosity ( Costes et al, 2019 ). In the present study, experimental participants manipulated the cursor by keystrokes, and the stimuli observed by the participants consisted of simple geometric patterns such as squares and circles.…”
Section: Introductionmentioning
confidence: 99%
“…The pseudo-haptic sensation [3,7] is produced by an appropriate sensory inconsistency between the physical movement of the body and the observed movement of a virtual pointer [4]. As for texture perception, some studies attempted to generate texture perception using the pseudo-haptic effects without sophisticated haptic devices [1,2,5,9,10]. Previously, we proposed a pseudo-haptic method for modulating the vibrotactile roughness of virtual surfaces during pen-surface interactions, and our user study showed the effectiveness of the proposed method [9].…”
Section: Introductionmentioning
confidence: 99%